Survival outcomes for HER2-low breast cancer: Danish national data - Michael Sode; Kåre Nielsen; Maj-Britt Jensen; Tobias Berg; Ann Knoop; Bent Ejlertsen; Anne-Vibeke Lænkholm (Acta Oncologica)
Background and purpose: We investigated the prognosis of breast cancer (BC) with low expression of human epidermal growth factor receptor 2 (HER2), as previous studies have found varying impacts on survival of HER2-low BC compared with HER2 0 BC (HER2 IHC score of 0). HER2-low is defined as a score of 1+ or 2+ in an immunohistochemical (IHC) assay without HER2 gene amplification.